Semiotic of teenage love in you are the apple of my eye - Maulana, Pandu; Fadillah, Dani (Universitas Ahmad Dahlan, 2024)
This study employs Roland Barthes semiotic approach to analyze the teenage love story in the film You Are the Apple of My Eye, focusing on the concepts of denotation, connotation, and myth. The aim of this research is to understand how the film constructs the meaning of teenage love through signs that encompass denotation, connotation, and social myths. This topic was chosen due to the important role that film plays in shaping adolescents' perceptions of emotional first love. The method used is qualitative semiotic analysis, which examines the visual elements, dialogue, and situations that portray the teenage love experience. The film employs cultural symbols that not only depict young love but also reinforce the social myth of first love as an unforgettable experience. The findings indicate that the film’s elements effectively combine denotative and connotative meanings, reflecting the emotional dynamics and conflicts of teenage love, while simultaneously reinforcing the myth of first love as a pivotal moment in life. This research contributes to cultural semiotic studies by providing insights into how popular media shapes and reinforces social myths through representations of teenage love.